Effects of quercetin and daidzein on egg quality, lipid metabolism, and cecal short-chain fatty acids in layers - Liu, Jiayan; Liu, Junhong; Zhou, Shuaishuai; Fu, Yuxin; Yang, Qinglin; Li, Yao (Frontiers in Veterinary Science, 2023)
In this study, the effects of quercetin and daidzein on egg quality, lipid metabolism, and cecal short chain fatty acids (SCFAs) were compared in layers. Hyline brown layers at 385 days of age with the similar laying rate (81.36% ± 0.62%) and body weight (2.10 kg ± 0.04 kg) were randomly divided into 3 treatments, 6 replicates per treatment, 20 layers each replicate. Layers in control, quercetin, and daidzein treatment were fed by basal diet supplemented with 0 mg/kg, 500 mg/kg quercetin and 30 mg/kg daidzein for 10 weeks. Results showed that eggshell strength and albumen height in week 4, egg yolk diameter in week 10, eggshell thickness and egg yolk height in week 4 and 10 were significantly increased in the quercetin treatment (P ≤ 0.05); content of phospholipid (PL), lecithin (LEC) in egg yolk and high density lipoprotein (HDL) content in serum were significantly increased, however, content of malondialdehyde (MDA), total cholesterol (TC), and triglyceride (TG) in egg yolk, content of TC, TG, low density lipoprotein (LDL), very low density lipoprotein (VLDL) in serum, and content of TC and TG in liver were significantly decreased in the quercetin treatment (P ≤ 0.05); content of isobutyric acid and valeric acid were significantly increased in cecum of the quercetin treatment (P ≤ 0.05), compared with control. Moreover, egg yolk height in week 10, eggshell thickness in week 4 and 10 were significantly increased in the daidzein treatment (P ≤ 0.05); content of MDA, TC, and TG in egg yolk, and TC, TG, VLDL in serum, and TC, TG in liver were significantly decreased in the daidzein treatment (P ≤ 0.05); HDL content was significantly increased in serum of the daidzein treatment (P ≤ 0.05), compared with control. However, daidzein did not affect SCFAs content in cecum. In conclusion, egg quality was improved by quercetin and daidzein through increasing antioxidant ability of egg yolk, and regulating lipid metabolism in layers. Quercetin worked better than daidzein in improving egg quality under this experimental condition.